2002
DOI: 10.1080/15216540214923
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Chondroitin/Dermatan Sulfate

Abstract: SummaryChondroitin sulfate and dermatan sulfate are synthesized as galactosaminoglycan polymers containing N-acetylgalactosmine alternating with glucuronic acid. The sugar residues are sulfated to varying degrees and positions depending upon the tissue sources and varying conditions of formation. Epimerization of any of the glucuronic acid residues to iduronic acid at the polymer level constitutes the formation of dermatan sulfate. Chondroitin/dermatan glycosaminoglycans are covalently attached by a common tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
234
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(250 citation statements)
references
References 48 publications
2
234
0
1
Order By: Relevance
“…(Funderburgh 2002;Silbert and Sugumaran 2002;Sugahara and Kitagawa 2002) Studies employing several methods of identification showed that the TM expresses a number of proteoglycans (PGs) ( Table 1). This includes a number of SLRPs, CSPGs, HSPGs, and other types of PGs (Table 1).…”
Section: Proteoglycansmentioning
confidence: 99%
“…(Funderburgh 2002;Silbert and Sugumaran 2002;Sugahara and Kitagawa 2002) Studies employing several methods of identification showed that the TM expresses a number of proteoglycans (PGs) ( Table 1). This includes a number of SLRPs, CSPGs, HSPGs, and other types of PGs (Table 1).…”
Section: Proteoglycansmentioning
confidence: 99%
“…Here we describe first the enzymes responsible for the synthesis of the HS repeating disaccharide region and then those for HS chain initiation in the chronological order of their discoveries. For the details of the CS/DS-synthesizing enzymes, see the article by Sugumaran and Silbert (44) in this issue.…”
Section: Initiation and Synthesis Of The Repeating Disaccharide Regiomentioning
confidence: 99%
“…Chondroitin sulfate (CS) and dermatan sulfate (DS) are also found ubiquitously in the extracellular matrices and at cell surfaces, being main components of cartilage and skin, respectively. CS consists of repeating disaccharide units of -4Gl-cUA␤1-3GalNAc␤1-, whereas DS is an isomeric form of CS and is formed from precursor CS through the action of glucuronyl C5 epimerase, thus consisting of disaccharide units of -4Gl-cUA␤1-3GalNAc␤1-and -4IdoUA␣1-3GalNAc␤1-in varying proportions (2). These disaccharide units are modified during chain elongation by specific sulfotransferases at C-2 of GlcUA/ IdoUA and/or C-4 and/or C-6 of GalNAc in various combinations, producing characteristic sulfation patterns critical for binding to various functional proteins displaying enormous structural diversity, comparable with that of HS, by embedding multiple overlapping functional sequences (3).…”
mentioning
confidence: 99%